2(5-x)=6-(2x-4)

Simple and best practice solution for 2(5-x)=6-(2x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5-x)=6-(2x-4) equation:


Simplifying
2(5 + -1x) = 6 + -1(2x + -4)
(5 * 2 + -1x * 2) = 6 + -1(2x + -4)
(10 + -2x) = 6 + -1(2x + -4)

Reorder the terms:
10 + -2x = 6 + -1(-4 + 2x)
10 + -2x = 6 + (-4 * -1 + 2x * -1)
10 + -2x = 6 + (4 + -2x)

Combine like terms: 6 + 4 = 10
10 + -2x = 10 + -2x

Add '-10' to each side of the equation.
10 + -10 + -2x = 10 + -10 + -2x

Combine like terms: 10 + -10 = 0
0 + -2x = 10 + -10 + -2x
-2x = 10 + -10 + -2x

Combine like terms: 10 + -10 = 0
-2x = 0 + -2x
-2x = -2x

Add '2x' to each side of the equation.
-2x + 2x = -2x + 2x

Combine like terms: -2x + 2x = 0
0 = -2x + 2x

Combine like terms: -2x + 2x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3-9(5x+2)=8 | | -7x=2/3 | | -k-(-5k)+9+2k-14= | | 14xy+7x-2y=0 | | 3(5a+3)-6= | | (3a+5b)(9a-12b)= | | 6x-4x+2=16-4 | | (5x^2y^2-9xy-6)(-3x^2y)= | | 18x-12=-7(8+x)-5(2-5x) | | 13=65 | | 9k-11+2k-7-4k= | | 24h^4x^3+48h^4x^2=0 | | 13x+y=15 | | 3(2y-0.3)=194-y | | 7+-3v=7+x | | 5(2z-3)=9(2+3) | | 2(x+5)=3-2(5+x) | | 9m+3=84 | | 5x^3(2x^4+4x^2+7x-2)= | | 29X+7=5(X+7) | | 904,320/x=113,040 | | x/10=-22/5 | | -(r-5-4p)= | | 8r+2r-5r--19r+4r=16 | | x + 3y = 10 | | 0.75a=14.25 | | -(0.6)(-0.3x)(1.5)(-1)=b | | (7x^3-15x^2-9)-(3x^3+5x+15)= | | 8b^5+20b^3+2b^2+12b=0 | | 2(x-5)=3-2(7-x) | | 20=s-25 | | 7x+1=2-x |

Equations solver categories